Periodontitis is a factor associated with dyslipidemia. (11th February 2021) - Gomes‐Filho, Isaac Suzart; Oliveira, Michelle Teixeira; Cruz, Simone Seixas da; Cerqueira, Eneida de Moraes Marcílio; Trindade, Soraya Castro; Vieira, Graciete Oliveira; Couto Souza, Paulo Henrique; Adan, Luis Fernando Fernandes; Hintz, Alexandre Marcelo; Passos‐Soares, Johelle de Santana; Scannapieco, Frank Andrew; Loomer, Peter Michael; et al.
Abstract: Objective: To investigate the association between the severity of periodontitis (exposure) and dyslipidemia (outcome). Methods: This was a cross‐sectional study of users of public health services. Periodontitis was defined using the Center for Disease Prevention and Control and the American Academy of Periodontology criteria. Lipid evaluation used data on systemic biomarkers. Dyslipidemia diagnosis was based on the Guidelines of total cardiovascular risk of the World Health Organization. Weight, height, waist circumference, and blood pressure were measured, and socioeconomic–demographic, lifestyle behavior factors, general and oral health conditions of the participants were collected. Hierarchical and logistic regression analyzes were used to determine the association between the exposures and the outcome. Odds Ratios, unadjusted and adjusted, and 95% confidence intervals were estimated. Results: Of 1, 011 individuals examined, 75.17% had dyslipidemia, and 84.17% had periodontitis, 0.2% with mild, 48.56% moderate, and 35.41% severe disease. The association between periodontitis and dyslipidemia was maintained through hierarchical analysis and in the multiple regression modeling, showing that the occurrences of dyslipidemia in the group with periodontitis, and its moderate and severe levels, were, respectively, 14%, 30%, and 16% higher compared with those without periodontitis. Conclusions: The results showed a positive association between moderate and severe periodontitis and dyslipidemia.